2023
DOI: 10.3390/nu15143235
|View full text |Cite
|
Sign up to set email alerts
|

Association between an Anti-Inflammatory Dietary Score and Periodontitis—Evidence from the Population-Based Hamburg City Health Study

Abstract: While the effects of dietary patterns on cardiovascular risk and diabetes have been well studied, the evidence is scarce as to which diet has the greatest anti-inflammatory potential and how dietary patterns are associated with periodontitis. In the Hamburg City Health Study (HCHS), we developed an anti-inflammatory dietary score using a data-driven approach based on the relationship of relevant selected food groups with inflammatory biomarkers (hsCRP and IL-6). The aim of this cross-sectional study was to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…We have previously shown that periodontitis was associated with cardiovascular risk and higher C-reactive protein concentrations ( 41 ) . Owing to the relation between diet and chronic inflammation, several studies reported associations between Dietary Inflammatory Index and periodontitis ( 6 , 7 , 11 ) and more lost teeth ( 17 ) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that periodontitis was associated with cardiovascular risk and higher C-reactive protein concentrations ( 41 ) . Owing to the relation between diet and chronic inflammation, several studies reported associations between Dietary Inflammatory Index and periodontitis ( 6 , 7 , 11 ) and more lost teeth ( 17 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have attempted to assess the relationship between overall diet and periodontitis ( 5 11 ) . Most studies have used hypothesis-driven dietary patterns based on a priori indices, such as indices derived using intake of foods and nutrients correlated with inflammatory biomarkers, e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial evidence suggests that interventions targeting lifestyle behaviors are effective, underscoring the importance of behavioral support in managing periodontitis [ 12 ]. Significant factors such as diet and smoking have been thoroughly investigated regarding their role in the risk of periodontal tissue decay [ 13 , 14 ]. Nevertheless, there is limited research on the potential role of exercise in preventing periodontitis.…”
Section: Introductionmentioning
confidence: 99%